El ideal de bienestar: Un pretexto para la des-responsabilización (2020)
This article shows a reflection about the way the actual society reigns a welfare ideality that sometimes drives people to des- responsibility about their acts. Our interest for writing about this topic comes up from listening to expectations that people generally mention when they demand a psychological attention, individually as well as in group. To develop the actual topic, two factors will be approached: first of all, we mention some examples about the psychological, social, educational, and so on, that reign this ideality. Afterwards, we imply the responsibility as an alternative to the des-responsibility. Finally, we propose that the psychological interventions, more than creating solutions and answers with respect to the complains, take the people to get questions that would become reflection vehicles, and therefore, they generate answers and actions.